STUDENTS’ PARTICIPATION IN SCIENTIFIC RESEARCH - Dmitry V. Shmuratko (Высшее образование в России)
The article deals with the organizational, methodological and legal aspects of students’ participation in fundamental scientific research. The analysis of scientific research areas, which students are involved in, is presented (for example, research projects in the framework of the strategic development of the Perm State Humanitarian Pedagogical University). Students’ publication activity in Permian leading scientific journals in 2011 is shown.